Associations with health-related quality of life after intracerebral haemorrhage: pooled analysis of INTERACT studies. Issue 1 (21st October 2016) - Delcourt, Candice; Zheng, Danni; Chen, Xiaoying; Hackett, Maree; Arima, Hisatomi; Hata, Jun; Heeley, Emma; Al-Shahi Salman, Rustam; Woodward, Mark; Huang, Yining; Robinson, Thompson; Lavados, Pablo M; et al.
Abstract : Background and purpose: Limited data exist on health-related quality of life (HRQoL) after intracerebral haemorrhage (ICH). We aimed to determine baseline factors associated with HRQoL among participants of the pilot and main phases of the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trials (INTERACT 1 and 2). Methods: The INTERACT studies were randomised controlled trials of early intensive blood pressure (BP) lowering in patients with ICH (<6 hours) and elevated systolic BP (150–220 mm Hg). HRQoL was determined using the European Quality of Life Scale (EQ-5D) at 90 days, completed by patients or proxy responders. Binary logistic regression analyses were performed to identify factors associated with poor overall HRQoL. Results: 2756 patients were included. Demographic, clinical and radiological factors associated with lower EQ-5D utility score were age, randomisation outside of China, antithrombotic use, high baseline National Institutes of Health Stroke Scale (NIHSS) score, larger ICH, presence of intraventricular extension and use of proxy responders. High (≥14) NIHSS score, larger ICH and proxy responders were associated with low scores in all five dimensions of the EQ-5D. The NIHSS score had a strong association with poor HRQoL (p<0.001). Female gender and antithrombotic use were associated with decreased scores in dimensions of pain/discomfort and usual activity, respectively. Conclusions: Poor HRQoL was associated with age, comorbidities, proxy source of assessment, clinical severity and ICH characteristics. The strongest association was with initial clinical severity defined by high NIHSS score. Trial registration numbers: NCT00226096 and NCT00716079 ; Post-results.